Milky Blood and Bloody Stools: A Twist Of Fate Spotting Of Neonatal Hyperlipoproteinemia - Venugopal, Aishwarya; Rahul, Aswathy; Sujatha, Radhika; Duraisamy, Prakash; Anupriya, A V; Kumar, Nikhil; Nema, Meghna (Indian Journal of Child Health, 2025)
Hyperlipoproteinemia is a very rare condition in a neonate and its mechanism includes lipoprotein molecular defect, lipoprotein lipase deficiency, or lipoprotein receptor defect. The common ones are familial combined hyperlipidemias, familial & polygenic hypercholesterolemia and familial hypertriglyceridemia. Usually, the detection is by accidental observation of milky blood while sampling for non-specific symptoms. Hyperlipoproteinemia can cause acute pancreatitis and early-onset cardiovascular disease if left untreated. Here we are reporting the case of a 25-day-old baby who presented with blood in stools. Physical examination was normal. Incidentally, it was found that the blood was highly viscous and milky. Complete lipid profile done suggested familial combined hyperlipidemia. The baby was started on Gemfibrozil (20 mg/kg twice daily) and continued on exclusive breast feeds along with the addition of medium chain triglyceride oil and multivitamins. Lipoprotein levels normalized within 5 months. This condition requires lifelong follow up.